[Letter from the Office of Personnel Management to Terence Golden, administrator for the General Services Administration] (Tufts Archival Research Center, 2007)
Letter from the Office of Personnel Management to Terence Golden, administrator for the General Services Administration (GSA). Expresses support for GSA workplace smoking restrictions. Recommends a decentralized policy for employee office space, in which decisions are left to the discretion of agencies. Suggests workplace smoking policies should be accompanied by smoking cessation programs. Expresses support for the end, but not the means, of the GSA policy.